Determination and comparison of effective moisture diffusivity of carrot (core and cortex) during hot air drying. (13th December 2022) - Zheng, Zhaohui; Wei, Shuo; Xie, Weijun; Ren, Liuyang; Fan, Ben; Fu, Hanyu; Yang, Deyong
Abstract: The moisture content and shrinkage of a sample are often ignored when determining its effective moisture diffusivity (EMD), which will result in a larger error in simulating the dynamic moisture diffusion process during drying. This work aimed to determine the EMDs of cortex and core in axial and radial directions considering the combined influence of moisture content and shrinkage of material. The drying and shrinkage characteristics of cortex and core were investigated under different hot air drying conditions, and the EMDs of the cortex and core in different drying stages were determined by the slope method considering the moisture content and shrinkage. The results showed that the EMDs were dependent on the carrot component rather than its directions. The EMDs of the core and cortex were different. It decreased slowly at the early drying stage, and decreased sharply at the later drying stage, and increased with the hot air temperature increasing. A third order polynomial relationship was established to correlate the EMDs with the moisture content and hot air temperature ( R 2 > 0.9460), and was verified by experiments. The maximum weighted absolute percentage error of the moisture content from simulation and experiment was only 6.11%, more accurate than that based on a constant effective moisture diffusivity (CEMD) for characterizing the intrinsic moisture diffusion in carrot during drying. Practical applications: The EMD is an important parameter that characterizes intrinsic moisture diffusion in material and often used for modeling and calculation in food drying. The investigation methods developed in this study can be applied for determining the EMD of samples with shrinkage and variable moisture content. This study would be helpful for understanding the moisture transfer mechanism and optimizing operation conditions in carrot drying industry. Abstract : Process of determination of EMD of carrot.